The incidence of opportunistic infections in patients with psoriatic arthritis treated with biologic and targeted synthetic agents: A systematic review and meta-analysis - Vassilopoulos, Athanasios; Shehadeh, Fadi; Benitez, Gregorio; Kalligeros, Markos; Cunha, Joanne S.; Cunha, Cheston B.; Mylonakis, Eleftherios (Frontiers in Pharmacology, 2022)
Background: Biologic (bDMARD) and targeted synthetic (tsDMARD) disease-modifying anti-rheumatic drugs have broadened the treatment options and are increasingly used for patients with psoriatic arthritis (PsA). These agents block different pro-inflammatory cytokines or specific intracellular signaling pathways that promote inflammation and can place patients at risk of serious infections. We aimed to review the incidence of opportunistic infections (OIs) in patients with PsA who were treated with these agents. Methods: We searched PubMed and EMBASE through April 14, 2022 for randomized clinical trials evaluating bDMARD or tsDMARD in the treatment of PsA. Trials were eligible if they compared the effect of a bDMARD or tsDMARD with placebo and provided safety data. We used the Revised Cochrane risk-of-bias tool to assess the risk of bias among trials, and stratified the studies by mechanism of action (MOA) of the agents studied. Results: We included 47 studies in this analysis. A total of 17,197 patients received at least one dose of an agent of interest. The cumulative incidence of OIs by MOA was as follows: (a) JAK inhibitors: 2.72% (95% CI: 1.05% - 5.04%), (b) anti-IL-17: 1.18% (95% CI: 0.60% - 1.9%), (c) anti-IL-23: 0.24% (95% CI: 0.04% - 0.54%) and (d) anti-TNFs: 0.01% (95% CI: 0.00% - 0.21%). Based on their MOA, these agents are known to increase the risk of certain serious infections. The cumulative incidence of herpes zoster infection following treatment with JAK inhibitors (JAKi) was 2.53% (95% CI: 1.03% - 4.57%) and the cumulative incidence of opportunistic Candida spp. infections following treatment with anti-IL-17, was 0.97% (95% CI: 0.51% - 1.56%). Conclusion: The overall incidence of OIs among patients with PsA who were treated with biologic and targeted synthetic agents is low. However, careful monitoring is warranted for specific OIs such as herpes zoster infection following JAKi treatment, mucocutaneous candidiasis following anti-IL-17 treatment, and Mycobacterium tuberculosis infection following anti-TNF treatment.